Identifying spatial variability and complexity in wetland vegetation using an object-based approach. Issue 18 (16th September 2016) - Owers, Christopher J.; Rogers, Kerrylee; Woodroffe, Colin D.
ABSTRACT: Coastal wetland vegetation is complex in form and function. Accurately mapping the spatial variation of vegetation complexity within these ecosystems is important for identifying areas of high conservation value that provide essential ecosystem services. In this study we delineate wetland vegetation, particularly mangrove and saltmarsh, to a vegetative morphological level that identifies spatial complexity in vegetation structure. This was achieved by integrating light detection and ranging (Lidar) and aerial imagery with an object-based approach. The results demonstrate that this is an effective methodology to identify vegetation complexity, with all study sites having greater than 90% classification accuracy. These high classification accuracies were underpinned by the use of Lidar data that provide detailed structural information about vegetation that is not captured with aerial imagery. This research highlights the importance of identifying spatial variability in vegetation structure when considering the value of coastal ecosystems and the services they provide.